Essentials of Regional Anesthesia (Springer International Publishing, 2018)
The management of pain can often be achieved by medications, physical therapies, or by various procedural techniques that have evolved in recent decades. With the trend towards more outpatient surgeries and less invasive surgeries to decrease perioperative risk, perioperative time, and costs, the practice of anesthesia is evolving to utilize regional anesthesia techniques both for inpatients and outpatients. Regional anesthesia is being performed for outpatient surgeries, obstetric anesthesia, trauma, chronic pain states, and for acute post-operative pain management. Therefore, it is paramount for physicians and nurses practicing anesthesia to understand the essentials of regional anesthesia, its evolving techniques, and appropriate utilization of modern equipment and technology to provide care safely. Essentials of Regional Anesthesia, Second edition, is a concise, up-to-date, evidence-based handbook that enables every resident, physician and nurse to understand the basics of regional anesthesia and the standard of care guidelines for the practice of regional anesthesia in a comprehensive fashion. This new edition includes: · Updated and new chapters on Ambulatory, Critical Care, and Obstetrics topics · Full color, clear, detailed, anatomic drawings · Clinically relevant, practical aspects of regional anesthesia · International contributing authors who are experts in their field · Latest ultrasound techniques and images Review of 1st edition: "There are many books available on regional anesthesia, and the trend is either to focus on illustrations, forgoing any discussion, or on text descriptions, making them bulky and hard to read. This book maintains that perfect balance between text and illustrations. It is truly a master companion book on regional anesthesia." (Tariq M. Malik, Doody's Book Reviews, April, 2012).